Landuse effects on structural stability and soil organic carbon in the submontane areas of north-western Himalayas, India - KUMAR, VIJAY; SHARMA, K. R.; ARYA, VIVAK M.; SHARMA, VIKAS (Journal of Soil and Water Conservation, 2020)
The present investigation was undertaken to study the influence of different land use systems viz. forest, horticulture, agriculture, pasture and degraded land on soil organic carbon and structural stability in north-western Himalayas, India. The soil organic carbon (SOC) content was higher in pasture land (7.57 g kg-1) and was least in degraded lands (5.01 g kg-1), but bulk density and particle density was higher in degraded land. The maximum water holding capacity was higher in forest and least in degraded land in the surface and sub-surface layers. The dry and wet aggregate stability index and percent of aggregates in the 2.0 mm class was higher in pasture land than other land uses. The aggregate stability index from dry structure (ASId) and their corresponding wet aggregate stability index (ASIw) were related significantly (r = 0.999**).